"Comrade Mzala": Memory Construction and Legacy Preservation. (3rd July 2017) - Ngonyama, Percy
ABSTRACT: Adopting the broad inter-disciplinary concept of "memory" and its construction in a public sphere, I examine some of the ways in which memories of Jabulani Nobleman Nxumalo, known as "Comrade Mzala" in liberation struggle circles, have been constructed and kept alive since his passing. A leading activist of the ANC, MK and the SACP, Mzala succumbed to an illness in a London hospital on February 22, 1991. A number of commemorative events and other activities, including grass-roots and branch-level initiatives, media releases, memorial lectures, colloquia and speeches and tributary statements, are analysed. Their tone, emotion, style and implicit objectives are explored. Notwithstanding the ubiquitous recognition of Mzala's liberation struggle credentials and intellectual prowess, there is no homogeneity in the manner he is remembered and celebrated; nor is there agreement in the reading of Mzala in a post-apartheid South Africa and its associated political and socio- economic context. Moreover, whilst it is predominantly organisations and individuals within the Tripartite Alliance who have been the main proponents of remembering, honouring and memorialising Mzala, there are others, outside of the Alliance and even antagonistic, who find inspiration in his radical world outlook, work and persona; and often use their memory of Mzala to critique the current political and economic conjuncture.